Aplicação de Hidrogel poli(Acrilamida-co-acrilato) na remediação de solo degradado por sódio - Moreira, Vanessa Ohana Gomes (2021)
Soil salinization is related to important restrictions on land productivity. Excess exchangeable sodium is a serious form of degradation, affecting the physical attributes of the soil and hindering the development of plants. The objective of this study was to carry out an experiment in greenhouse conditions to evaluate the use of hydrogel synthesized in the laboratory based on acrylamide and potassium acrylate poly(acrylamide-co-acrylate) in the remediation of sodiumdegraded soil. For this, an experiment was carried out in a completely randomized design, in a 2x4 factorial scheme, in which the soil was incubated with the polymer for different periods. Soil samples with an unreserved structure of the superficial layer (0 - 0.18 m) and subsurface (0.45 - 0.85 m) of Typical Sodium Fluvic Neossol were used and evaluations were carried out during 4 incubation periods, corresponding to 10 days, 4, 8 and 12 months (T0, T4, T8 and T12, respectively). The chemical analyzes consisted of the hydrogel decomposition to verify if there were changes in the absorption and release of sodium and potassium ions in the polymer structure. In addition, analyzes of the sodium and potassium ions were performed in the soluble extract of the substrate under incubation. Physical analyzes of soil density, total porosity, macro and microporosity, hydraulic conductivity of the substrate, degree of flocculation of the clays, stability and average and geometric diameter of the aggregates were carried out. The data obtained were subjected to analysis of variance (ANAVA) by the 1% F test, applying the Tukey test to compare means of the qualitative factor and regression analysis for the quantitative factor. When the interaction was significant, the analysis was performed to analyze the averages. From the results it was possible to infer that the hydrogel has the capacity to absorb sodium (Na+) from the soil, this process is dependent on the concentration of Na+ in the solution and on the incubation time, as the amount of the element has significantly reduced in the gel, in function of time, until it has stabilized. The soil macroporosity increased (resulting in 0.1454 and 0.1282 cm cm-3 for P1 and P2, respectively, in T12) and there was a reduction in microporosity and total porosity in both evaluated layers. There was an increase in the stability of larger aggregates (> 4.6 mm) in the superficial and subsurface layer (73.96% and 55, 99% for P1 and P2, respectively). However, in the superficial layer, the greater amount of organic matter may also have contributed to the greater aggregation of the soil. The polymer was not effective in improving the soil density (resulting in 1.53 and 1.66 g cm-3 for P1 and P2, respectively, in T12) and the hydraulic conductivity of the saturated soil (being null in both layers in the last evaluation period). It is suggested that its efficiency be verified when combined with another remediation technique for soils affected by sodium.